Asian Indians With Prediabetes Have Similar Skeletal Muscle Mass and Function to Those With Type 2 Diabetes - Sambashivaiah, Sucharita; Harridge, Stephen D. R.; Sharma, Nidhi; Selvam, Sumithra; Rohatgi, Priyanka; Kurpad, Anura V. (Frontiers in Nutrition, 2019)
Background: Type 2 Diabetes (T2D) is a major concern among Asian Indians, not least because many develop T2D at normal BMI (body mass index), and at relatively low body fat. Asian Indians are also relatively sarcopenic, but the role of skeletal muscle (mass or strength) in those with T2D has not been explored. Aim: The present study aimed to compare skeletal muscle mass, function and contractile quality between healthy controls, prediabetes (PD) and T2D middle aged non-obese Asian Indians. Methods: Adult males between the age of 20-50 years, consisting of healthy controls (n=44), PD (n=125) and T2D (n=55) were studied. Skeletal muscle mass was measured as the appendicular muscle mass (AMM) using Dual X-ray Absorptiometry (DXA). Isometric and dynamic muscle function was measured by isokinetic dynamometry (at 0, 60, 120, 180 degree/s). Muscle contractile quality was derived by dividing the peak muscle torque with the respective AMM. Fasting plasma glucose and insulin were used to derive insulin resistance (HOMA-IR). Results: The control group were on average 10 years younger than the other 2 groups (p<0.01). The age-adjusted mean values for AMM were similar across the 3 study groups. However, the age-adjusted mean muscle torque was significantly lower in both absolute and normalised isometric and isokinetic strength in PD and T2D groups compared to controls (p≤0.01), with the difference persisting even after adjusting for other covariates. However, there was no difference in muscle strength and contractile quality between the PD and T2D study groups. Conclusions: Muscle strength and contractile quality would appear to be sensitive and early indices of the trajectory towards diabetes, more so than skeletal muscle mass. It is thus important to recognise the importance of functional measurements among Asian Indians when considering the role of muscle in diabetes. The data also suggest that specific muscle conditioning (e.g. resistance training) might have efficacy in improving contractile quality as well as muscle mass, and thus aiding in the prevention of the trajectory towards the development of T2D.